Exploring the Complexities: Understanding the Clinicopathological Spectrum of Tuberculosis in the Head-and-neck Region - Sheereen, Shazima; Manva, Mohnish Zulfikar; Sheereen, Shamama; Patil, Namrata N. (International journal of mycobacteriology, 2024)
Introduction: Tuberculosis (TB) affecting the head-and-neck area can often resemble cancer, leading to misdiagnosis and delayed treatment. A better understanding of this condition is necessary for early diagnosis and prompt treatment initiation. This study examines the clinical and pathological characteristics of different types of TB in the head-and-neck region. Methods: This retrospective study analyzed patients diagnosed with TB in the head-and-neck region at a health center between January 1, 2018, and January 1, 2024. The study population consisted of patients who were diagnosed with TB of the head and neck. Results: The study analyzed data from 30 patients, comprising 14 (47%) males and 16 (53%) females, all of whom tested negative for HIV. Most cases (15, 50%) were observed in the age group of 15-24 years, with 5 (15.6%) subjects falling in the age bracket of 0-14 years. Among the types of lesions detected, cervical tubercular adenitis was the most frequently observed lesion, found in 22 (73%) subjects. Females are more susceptible to cervical tubercular adenitis, while males are more likely to experience laryngeal TB. Conclusion: The clinical manifestation of TB affecting the head-and-neck region can exhibit a diverse range of symptoms, which may lead to misinterpretation and diagnostic errors. Therefore, health-care practitioners must understand and include the condition in differential diagnoses.